2017
DOI: 10.1186/s12889-017-4379-4
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of adherence to micronutrient supplementation before and during pregnancy in Vietnam

Abstract: BackgroundPoor adherence to micronutrient supplementation often limits the effectiveness of public health programs. While predictors of adherence to micronutrient supplementation during pregnancy are well documented, information on adherence to preconception supplements is scarce. The objective of this study was to describe the predictors of adherence to preconception and prenatal micronutrient supplementation among women participating in a randomized control trial in Vietnam.MethodsAdherence data were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 24 publications
2
21
1
Order By: Relevance
“…Also, the improvement made on maternal health-seeking behaviour and ANC visit might be the reason to increase the level of adherence in this setting. This estimate was also lower compared with the reports in Vietnam, 82% [9] and Niger,68% [61]. The observed variation might be due to the differences in socio-demographic characteristics and knowledge of IFA supplementation [62].…”
Section: Discussionmentioning
confidence: 57%
“…Also, the improvement made on maternal health-seeking behaviour and ANC visit might be the reason to increase the level of adherence in this setting. This estimate was also lower compared with the reports in Vietnam, 82% [9] and Niger,68% [61]. The observed variation might be due to the differences in socio-demographic characteristics and knowledge of IFA supplementation [62].…”
Section: Discussionmentioning
confidence: 57%
“…Compliance with the intervention both before and during pregnancy was also very high (>90%) and did not differ by treatment group (32). Second, the use of standardized protocols, an efficient monitoring and supervision system, and well-trained field staff also contributed to the internal validity of our results.…”
Section: Discussionmentioning
confidence: 81%
“…Both a lack of antenatal care attendance and lack of full awareness in health professionals contribute to the low prevalence of correct FA supplementation during the periconceptional period. A randomized controlled trial on prenatal micronutrient supplements indicated a positive relationship between the number of community health worker visits and adherence to prenatal supplementation in Vietnam [26]. These findings suggest that the support of community health services may improve the prevalence of correct FA supplementation recommended by the WHO.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of NTDs declined slightly from 62.1 per 100,000 live births to 61.7 per 100,000 live births during the past 10 years (from 2007 to 2017), but was still higher than the corresponding rates in Singapore (12.4 per 100,000 live births) and Cambodia (45.3 per 100,000 live births) in 2017 [23]. The awareness of the importance of FA prior to conception and during early pregnancy is low, and little information is available on the coverage of supplementation with FA during this period [24,25,26,27]. Studies that reported the coverage of FA supplementation were not able to assess the frequency and duration of supplementation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation